Challenges and Advances in Bee Health and Diseases - Giovanni Cilia; Antonio Nanetti (Veterinary Sciences, 2023)
Understanding the health status of bees is crucial in assessing the epidemiology of pathogens that cause diseases in honey bee (Apis mellifera) colonies and wild bees [...]